Electrochemical construction of Cu@NF frameworks and synthesis of self-supported microflower Cu2S@NF as bifunctional catalysts for overall water splitting. (26th April 2022) - Han, Zhiyue; Li, Guotong; Zeng, Xin; Zhu, Yanli; Li, Nan; Zhang, Jiatao; Zhao, Wanjun; Jiao, Qingjie
Abstract: A two-step electrochemical method is proposed for the in-situ deposition of copper and synthesis of copper(Ⅰ) sulfide (Cu2 S) with controllable morphology on nickel foam (NF), and the thus-prepared self-supported Cu2 S@NF electrodes exhibit excellent performance as bifunctional electrocatalysts. Characterizations with scanning electron microscopy show rock-shape of the deposited copper through potentiostatic method, which can be further sulfurized to microflower morphology by a unique underpotential electrochemical method. The size and amount of the deposits can be adjusted by controlling applied potentials, leading to the optimization of electrocatalytic activity. The Cu2 S@NF exhibits superior electrocatalytic performance towards HER and OER in 1 M KOH with the low overpotentials of 105 mV and 194 mV at 10 mA/cm 2, as well as small Tafel slopes of 92.89 mV/dec and 72.81 mV/dec, respectively. This work provides a simple method for the synthesis of efficient catalysts, which can be extended to the fabrication of other transition metal-based electrocatalysts. Highlights: An electrochemical method is proposed to fabricate Cu@NF and Cu2 S@NF catalysts. Copper can be sulfurized at a negative potential in the presence of S 2− . Cu2 S@NF exhibits excellent catalytic activity towards both HER and OER. Catalytic performance can be optimized by controlling electrochemical parameters.